Perinatal factors impacting echocardiographic left ventricular measurement in small for gestational age infants: a prospective cohort study - Ibrahim Elmakaty; Ahmed Amarah; Michael Henry; Manoj Chhabra; Danthanh Hoang; Debbie Suk; Nitin Ron; Beata Dygulska; Farrah Sy; Madhu B. Gudavalli; Ali M. Nadroo; Pramod Narula; et al. (BMC, 2023)
Abstract Introduction Infants born small for gestational age (SGA) have an increased risk of developing various cardiovascular complications. While many influencing factors can be adjusted or adapt over time, congenital factors also have a significant role. This study, therefore, seeks to explore the effect of perinatal factors on the left ventricular (LV) parameters in SGA infants, as assessed immediately after birth. Methods and materials This single-center prospective cohort study, conducted between 2014 and 2018, involved healthy SGA newborns born > 35 weeks' gestation, delivered at New York-Presbyterian Brooklyn Methodist Hospital, and a gestational age (GA)-matched control group of appropriate for gestational age (AGA) infants. Data analysis was performed using multivariate linear regression in STATA. Results The study enrolled 528 neonates, 114 SGA and 414 AGA. SGA infants exhibited a mean GA of 38.05 weeks (vs. 38.54), higher male representation (69.3% vs. 51.5%), lower birth weight (BW) (2318g vs 3381g), lower Apgar scores at birth, and a higher rate of neonatal intensive care unit admission compared to AGA infants (41.2% vs.18.9%; p<0.001). Furthermore, SGA infants were more likely to be born to nulliparous women (63.16% vs. 38.16%; p<0.001), with lower body mass index (BMI) (29.8 vs. 31.7; p=0.004), a lower prevalence of gestational maternal diabetes (GDM) (14.9 % vs. 35.5%; p<0.001), and a higher prevalence of preeclampsia (18.4 % vs. 6.52%; p<0.001). BW was identified as the most significant predictor affecting most LV parameters in this study (p<0.001), except shortening fraction, asymmetric interventricular septal hypertrophy and Inter-ventricular septal thickness/LV posterior wall ratio (IVS/LVPW). Lower GA (coefficient = -0.09, p=0.002), insulin use in GDM (coefficient = 0.39, p=0.014), and low APGAR scores at 1 minute (coefficient = -0.07, p<0.001) were significant predictors of IVS during diastole (R-squared [R2]=0.24). High maternal BMI is marginally associated with LVPW during systole (R2=0.27, coefficient = 0.01, p=0.050), while male sex was a significant predictor of LV internal dimension during diastole (R2=0.29, p=0.033). Conclusion This study highlights the significant influence of perinatal factors on LV parameters in SGA infants, with BW being the most influential factor. Although LV morphology alone may not predict future cardiovascular risk in the SGA population, further research is needed to develop effective strategies for long-term cardiovascular health management in this population.